WESTERN METHODOLOGY TO STUDY RELIGION WITH SPECIAL REFERENCE TO COMPARATIVE RELIGION - Malik, Mohd Ashraf (Universitas Islam Indonesia, 2020)
The systematic study and comparison of religions have traversed a long path since Max Muller wrote Comparative Mythology in 1856. Muller had predicted about the ‘Science of Religion’ (Religionswissenschaft) as the ‘Science’ that is based on an impartial and truly scientific comparison of all, or at all events, of the most important religions of mankind. Such an approach was developed in contrast to the reductionist tendencies as found in the anthropological, sociological and psychological theories put forward by the scholars as E. B. Tylor, James Frazer, Herbert Spencer, Emile Durkheim, and Sigmund Freud, etc. The process of studying religions comparatively implied the understanding and appreciation for the religious phenomenon without passing any judgement on the religion studied. In the succeeding pages we will be discussing and analysing the approach and method known as phenomenological method in the study of religions. Such a method is a modified or revised form of comparative religion methodology as was envisioned by Max Muller in the 19th century.